Employment of critical success factors in achieving the strategy Entrepreneurship: A field research for my company Oil Products Distribution and Midland Refineries - حمادي, انتصار عباس; سلمان, مهند كاظم (Journal of Economics and Administrative Sciences, 2016)
Abstract        The critical success factors of the means of the most modern in determining the main directions for organizations to achieve competitive advantage. and can be a critical success factors in organizations that overlap in the functional areas of the organization. that successful organizations use these factors to get to the uniqueness and distinction. as the entrance of critical success factors with the capacity Evaluative phase correction because discovery increases the perception of managers of what is important to the organization and using them to get to the Strategic Entrepreneurship. as it begins in terms of permanence of success and be accompanied by the first move in the midst of the information revolution and its ability to withstand the calculated risk and be accompanied by constant renewal and adaptation in light environments, complex dynamics, particularly in the Iraqi environment in especially after the total reliance on oil exports for economic growth of the country. from here came the idea of ​​research in a field research for the oil sector companies, including "oil products distribution company and middle refinery"  of the importance of these organizations in the first place in terms of the production of oil derivatives through refining and delivery of those products to the citizen and filling economic need of the country in general, any researcher organizations to the fact that, one complementary to the other in terms of providing the public service and the other to provide goods and products and It is then mainstays of the Ministry of Oil and the consolidation of the importance of the role played by these organizations on the availability of critical success factors across its operations (Strategic orientation, Top management support, resources, of governance) and employed to achieve Strategic Entrepreneurship its components (Innovation, proactive, risk taking, flexibility) For the purpose of achieving the goal of the research and answer questions about the problem after the application of research on a sample of (131) manager of both organizations. surveyed, research has come to a total of The most important conclusions of the surveyed organizations have hired critical success factors in achieving Strategic Entrepreneurship with significant differences between them in addition to having a significant effect relationship between the variables of moral search.